Membangun Kepercayaan Publik Melalui Kebijakan Sosial Inklusif - Wahyuningsih, Rutiana Dwi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2011)
Social policy is an important instrument in building public trust. However, fail to adopt appropriate approach in formulating and developing social policy may result in the public distrust toward government as the main actor of social policy making. With the case of participatory city planning in Surakarta, this article argues that democratic and inclusive social policies, since the policy formulation to the evaluation, will contribute positively in building public trust, which in turn increases the governance effectivity.